2009
DOI: 10.1002/jcop.20345
|View full text |Cite
|
Sign up to set email alerts
|

Tuning in to kids: an emotion‐focused parenting program—initial findings from a community trial

Abstract: This study evaluated a new group parenting program, Tuning in to Kids, which taught emotion coaching skills to parents of preschool children. In a randomized control trial, 218 primary caregiver parents of children aged 4.0-5.11 years completed questionnaires assessing parent emotion socialization (emotion coaching vs. emotion dismissing), parent emotional competence, parent wellbeing and child behavior. Assessment occurred at preintervention and 10 weeks later. Parents randomized to the intervention condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
3
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 32 publications
8
66
3
3
Order By: Relevance
“…When mothers felt able to regulate their own negative moods and maintain positive emotions, they displayed more supportive reactions (such as problem-focused responses and encouragement) and less nonsupportive reactions (such as distress) to child's negative emotions. These results are in accordance with previous studies suggesting that parents' cognitions of Journal of Behavioral and Brain Science their own affects and emotional wellbeing are core characteristics to be available and responsive to their child's emotions [19] [20] [21].…”
Section: Introductionsupporting
confidence: 93%
“…When mothers felt able to regulate their own negative moods and maintain positive emotions, they displayed more supportive reactions (such as problem-focused responses and encouragement) and less nonsupportive reactions (such as distress) to child's negative emotions. These results are in accordance with previous studies suggesting that parents' cognitions of Journal of Behavioral and Brain Science their own affects and emotional wellbeing are core characteristics to be available and responsive to their child's emotions [19] [20] [21].…”
Section: Introductionsupporting
confidence: 93%
“…In their theoretical model, Eisenberg et al (1998) suggested that parental ERSBs could be influenced by parents' characteristics, such as parental regulation and emotionality, and by children's characteristics, such as children's personality. Moreover, parents' cognition of their own affect and emotional wellbeing, including their ability to express and regulate their own emotions, are core characteristics of availability and responsiveness to children's emotionality (Gottman, Katz, & Hooven, 1996, 1997Havighurst et al, 2009). …”
Section: Why It Is Relevant To Explore the Variability Of Parentalmentioning
confidence: 99%
“…Regarding parents' characteristics, we took into account parents' age, level of education and factors of openness to emotional processes. As parents' emotional wellbeing is important to an appropriate response to their children's emotional needs (Havighurst et al 2009), we expected ERSBs to vary according to specific factors of parents' openness to emotional processes. For example, parents who communicated about their own emotion would be more likely to discuss emotions with their ASD children.…”
Section: Objectives Of the Present Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The parent intervention was the Tuning in to Kids (TIK) program (see Havighurst et al 2009, for further detail) extended so that it was delivered across eight, 2 h sessions by two facilitators. Traditional behavioral parenting interventions suggest that parents need to change their way of responding to children's behavior.…”
Section: Parent Componentmentioning
confidence: 99%